P183 Monitoring of candida colonization in the respiratory tract of COVID-19 cases. (20th September 2022) - Diba, Kambiz; Makhdoomi, Khadige; Nejadrahim, Rahim; Namaki, Atefeh
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Objectives: Opportunistic yeasts potentially cause infection or colonization in the lower respiratory tract. Candida albicans is a common agent of yeast infections but other yeasts such as non- albicans Candida are important as resistant fungi to antifungal drugs. The predisposing factors for the overgrowth and invasion by Candida species include corticosteroid therapies, long-time hospitalization, antibiotic therapies, and primary infections by Mycobacterium tuberculosis and viral agents. The screening of Candida colonization in the lower respiratory tract of the cases with a history of COVID-19 was performed in this study at a great training hospital in Northwest of Iran. Methods: During the pandemic COVID-19, about 445 cases with severe COVID-19 hospitalized and used dexamethasone were investigated for Candida infections and colonization by the laboratory data of Medical Mycology Center, UMS University, Urmia, Iran. Our subjects were sputum, bronco-alveolar and bronchial specimens. Candida elements including pseudo-hypha and blasto-spores microscopically were investigated. Differential cultures and PCR-RFLP were used for the identification of Candida yeasts at the level of species. Results: Totally, 54 yeast overgrowth was detected in the clinical specimens including Candida albicans 28 (51.8%), non- albicans Candida species 24 (44.4%) and a case of Pneumocystis jirovecci . All of the cases with Candida detections were Covid-19 positive. Moreover, two cases of rhino-cerebral Mucomycosis, two cases of TB, two cases of asthma, and one case of cystic fibrosis were included. Conclusion: As a conclusion, Fungi especially Candida yeasts be considered as the potential pathogens in cases with a history of severe COVID-19 and corticosteroid therapy during stay at the hospital.